An evaluation of two methods of bacteriocine typing of organisms of the genus Proteus. - Al-Jumaili, I J (1975)
An assessment of two simple methods of typing Proteus isolates using bacteriocines is described. The methods chosen were those of Cradock-Watson and Al-Jumaili. It has been shown that the use of liquid bacteriocine preparations is more satisfactory than methods involving proteocine production in solid media. For example, no non-typable isolates were encountered and a large number of strains were demonstrated. This method is therefore proposed for use in a routine diagnostic laboratory.